A non-randomized, open-label study to assess the impact of rounds of mass drug administration with artemisinin-piperaquine plus primaquine on malaria in São Tomé Island - Mingqiang Li; Ruixiang Tan; Peiting Chen; Herodes Sacramento Rampao; Carlos Alberto Bandeira D’almeida; Guoming Li; Jingwen Liu; Guozhuang Shi; Fei Chen; Lei Shu; Xinan Huang; Changsheng Deng; et al. (Parasites & Vectors)
Abstract Background The aim of this study was to explore the effect of mass drug administration (MDA) on malaria transmission in low-endemic malaria areas. Methods Mass drug administration of artemisinin-piperaquine (AP) + primaquine (PMQ) was targeted to 17,438 individuals in the Agua Grande region of São Tomé and Príncipe (STP). The participants were allocated to either a three-round MDA (3-MDA) group or to a two-round MDA (2-MDA) group. The coverage rate, compliance, adverse events and other indicators were evaluated. Results Mass drug administration coverage rate in the 3-MDA group (20,548 person-times) was 84.23–89.14%, with a compliance of 68.38%. MDA coverage rate in the 2-MDA group (15,365 person-times) was 87.30–93.23%, with a compliance of 80.70%. The rates of MDA-related adverse reactions were low in both the 3-MDA (0.75%) and 2-MDA (0.72%) groups, and no serious adverse reactions were observed. Malaria incidence decreased by 80.47% (z = − 2.35, P = 0.019) and 72.27% (z = − 0.89, P = 0.372) in the 3-MDA and 2-MDA groups, respectively, within 1 year. Conclusions Two or three rounds of MDA with AP and PMQ in STP safely and rapidly reduced the prevalence of malaria cases and infections. It is possible that two rounds of MDA in certain districts may achieve the desired outcomes. Graphical Abstract